PERLINDUNGAN HUKUM KONSUMEN TERHADAP SISTEM PEMBAYARAN CASH ON DELIVERY DALAM TRANSAKSI JUAL BELI E-COMMERCE - Diana Rosalina; Rara Amalia (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2025)
The Cash On Delivery (COD) payment system has become one of the most popular payment methods in e-commerce transactions in Indonesia. Despite its convenience, the COD system carries potential legal issues, particularly regarding consumer protection. This research uses a qualitative method with a normative juridical and conceptual approach. The regulation of the COD payment system in e-commerce transactions under Indonesia’s positive law is governed, among others, by the Indonesian Civil Code (KUHPerdata), Law Number 8 of 1999 concerning Consumer Protection, Law Number 1 of 2024 on Electronic Transactions, and Government Regulation Number 80 of 2019 concerning Trade Through Electronic Systems. Legal protection for consumers using the COD method remains limited, and the lack of public awareness about COD mechanisms increases risks for consumers. Consumers may file claims against business actors, and Article 45 paragraph 2 of the Consumer Protection Law stipulates that consumers may also resolve disputes outside of court or through non-litigation channels. The government and policymakers need to formulate specific regulations governing e-commerce transactions using the COD system, including the protection of consumer rights, the obligations of business actors, and the responsibilities of intermediaries. Consumers are expected to be more cautious and critical when conducting e-commerce transactions. The government must be proactive in promoting the use of Online Dispute Resolution (ODR) in cases involving electronic transaction disputes.